BEEF CATTLE MUSCULARITY CANDIDATE GENES - Irida Novianti; Waynes S. Pitchford; Cynthia D. K. Bottema (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
Muscularity is a potential indicator for the selection of more productive cattle. Mapping quantitative trait loci (QTL) for traits related to muscularity is useful to identify the genomic regions where the genes affecting muscularity reside. QTL analysis from a Limousin-Jersey double backcross herd was conducted using QTL Express software with cohort and breed as the fixed effects. Nine QTL suggested to have an association with muscularity were identified on cattle chromosomes BTA 1, 2, 3, 4, 5, 8, 12, 14 and 17. The myostatin gene is located at the centromeric end of chromosome 2 and not surprisingly, the Limousin myostatin F94L variant accounted for the QTL on BTA2. However, when the myostatin F94L genotype was included as an additional fixed effect, the QTL on BTA17 was also no longer significant. This result suggests that there may be gene(s) that have epistatic effects with myostatin located on cattle chromosome 17. Based on the position of the QTL in base pairs, all the genes that reside in the region were determined using the Ensembl data base (www.ensembl.org). There were two potential candidate genes residing within these QTL regions were selected. They were Smad nuclear interacting protein 1 (SNIP1) and similar to follistatin-like 5 (FSTL5). (JIIPB 2010 Vol 20 No 1: 1-10)